Answer:
Explanation:
(a). from the question, we are asked to prove that for any positive n integer
σk(n) = σ−k(n)n∧k
taking K as a natural number
we have that
σ-k(n) = Σₐ₋ₙa∧k = Σₐ₋ₙ (n/a)∧-k
σ-k(n) = Σₐ₋ₙ (n/a)∧-k = Σₐ₋ₙ (a/n)∧k
= Σₐ₋ₙ (a∧k/n∧k)
given that n∧k.σ-k(n) = Σₐ₋ₙ a∧k = σk(n)
prove : σk(n) = σ-k(n)*n∧k
(b). from the question, our positive integer is n
we have a convergent sequence in an increasing order given as
(1 + 1/2 + 1/3 + --------+ 1/n - log (n+1)) ≥ 1
which is now thus
₹ = lim → ∞ (1 + 1/2 + 1/3 + --------+ 1/n - log (n+1))
∴ for all values of n ≥1, 1 + 1/2 + 1/3 + --------+ 1/n - log (n+1) ≤ ₹
1 + 1/2 + 1/3 + --------+ 1/n ≤ ₹ + log (n+1) for all n≥ 1
recall that for natural numbers n in (a) i.e σ₁(n) : nσ₋₁(n)
σ₋₁(n) = Σₐ₋ₙ (1/a) ≤ Σn-i=1 (1) : ≤ ₹ + log(n + 1)
this gives σ₋₁(n) = nσ₋₁(n) ≤ n(log (n + 1) + ₹)
Prove : σ₋₁(n) = n(log (n + 1) + n₹ for value of n ≥ 1
cheers i hope this helps